2019
DOI: 10.7197/223.vi.475189
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Demographical Features, Accompanying Diseases and Neutrophil to Lymphocyte Ratio- Platelet to Lymphocyte Ratio in Patients with Bullous Pemphigoid in Bolu

Abstract: Bullous pemphigoid (BP) is a rare autoimmune blistering disorder that affects the elderly population. In this study, we retrospectively evaluated the clinical, demographic characteristics and comorbid diseases in patients with BP. Mean platelet volume (MPV), neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) are known to be the indicators of inflammation. We also investigated MPV, NLR, and PLR values in patients with BP and a control group. To our knowledge, there is no previous study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The NLR was also found to be positively correlated with disease activity in rheumatoid arthritis, gouty arthritis, Sjögren's syndrome, familial Mediterranean fever, osteoarthritis, and other diseases [20,[35][36][37][38]]. An elevated NLR has been observed in patients with the dermatological disorders such as bullous pemphigoid [30], psoriasis [27], lichen planus [28], and atopic dermatitis compared to control groups [39]. Elevated NLR in psoriasis was also positively correlated with the Psoriasis Area and Severity Index (PASI) score and was described as a possible predictor for psoriatic arthritis [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NLR was also found to be positively correlated with disease activity in rheumatoid arthritis, gouty arthritis, Sjögren's syndrome, familial Mediterranean fever, osteoarthritis, and other diseases [20,[35][36][37][38]]. An elevated NLR has been observed in patients with the dermatological disorders such as bullous pemphigoid [30], psoriasis [27], lichen planus [28], and atopic dermatitis compared to control groups [39]. Elevated NLR in psoriasis was also positively correlated with the Psoriasis Area and Severity Index (PASI) score and was described as a possible predictor for psoriatic arthritis [40].…”
Section: Discussionmentioning
confidence: 99%
“…These include rheumatic diseases such as rheumatoid arthritis, lupus erythematosus, fibromyalgia [17,20,21], several types of vasculitides [22][23][24], cardiovascular diseases [25], malignancies [26], inflammatory skin disorders including psoriasis [27] and lichen planus [28]. The NLR and MPV were also described as possible markers of inflammation in bullous pemphigoid [29,30]. Two retrospective studies demonstrated that the NLR and PLR rates were higher in PV patients than in controls but were not related to disease severity and course [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Ozer et al [39] proved that the NLR levels of 26 untreated BP patients were signi cantly higher than that of age-and gender-matched 25 nonin ammatory dermatosis controls (p = 0.04). Similarly, in 2019, Sere ican et al [40] veri ed that the NLR levels of 14 untreated BP patients were signi cantly higher than that of age-and gender-matched 14 non-in ammatory dermatosis controls (p = 0.01).…”
Section: Discussionmentioning
confidence: 92%